2020
DOI: 10.1136/bmjopen-2020-037545
|View full text |Cite
|
Sign up to set email alerts
|

‘Only twice a year’: a qualitative exploration of 6-month antiretroviral treatment refills in adherence clubs for people living with HIV in Khayelitsha, South Africa

Abstract: ObjectiveLonger intervals between routine clinic visits and medication refills are part of patient-centred, differentiated service delivery (DSD). They have been shown to improve patient outcomes as well as optimise health services—vital as ‘universal test-and-treat’ targets increase numbers of HIV patients on antiretroviral treatment (ART). This qualitative study explored patient, healthcare worker and key informant experiences and perceptions of extending ART refill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
(29 reference statements)
3
29
0
Order By: Relevance
“…Reducing the frequency of AC visits ostensibly reduces the opportunity for peer and facilitator support, which patients have described as an important component of the AC model [10,13]. Paradoxically, in a qualitative sub‐study of our trial, patients reported that less frequent visits increased peer and facilitator support as AC members were able to set aside time for the visit and peer interaction if it was only twice a year [49]. Our sub‐analysis of AC patients on ART for less than three years at baseline suggests that extended dispensing intervals may result in inferior retention for this group, indicating more frequent group contact initially may support less frequent interaction later on.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the frequency of AC visits ostensibly reduces the opportunity for peer and facilitator support, which patients have described as an important component of the AC model [10,13]. Paradoxically, in a qualitative sub‐study of our trial, patients reported that less frequent visits increased peer and facilitator support as AC members were able to set aside time for the visit and peer interaction if it was only twice a year [49]. Our sub‐analysis of AC patients on ART for less than three years at baseline suggests that extended dispensing intervals may result in inferior retention for this group, indicating more frequent group contact initially may support less frequent interaction later on.…”
Section: Discussionmentioning
confidence: 99%
“…Other service delivery models, for example six‐monthly appointments with reduced frequency of clinic visits by increasing months between ART refills may reduce patient‐incurred costs further. However, preference for this model still varies showing the complexity of preferences [42‐44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results do not imply that second-and third-line patients should be separated from first-line patients, and where healthcare workers have been trained to manage different ART lines, these different groups of patients could be mixed. In CRAM, due to medication stock challenges, the clubs were meeting once per month, whereas in other settings, they were reconvening less regularly, for example every 2, 3 or 6 months [15,24,25]. Having less frequent sessions, when medication stocks allow, like in South Africa where patients reconvened every 6 months, proved to be more convenient for the patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…In CRAM, due to medication stock challenges, the clubs were meeting once per month, whereas in other settings, they were reconvening less regularly, for example every 2, 3 or 6 months [15,24,25]. Having less frequent sessions, when medication stocks allow, like in South Africa where patients reconvened every 6 months, proved to be more convenient for the patients [25]. Having longer intervals between club meetings would simultaneously create new slots for early morning clubs and enable recruiting of new patients.…”
Section: Discussionmentioning
confidence: 99%